A Review of Blockchain-Based E-Voting Systems: Enhancing Security and Transparency - Kabir Ahmed, Muhammed; Dangdat Delmut, Raymond; Habila, Mikailu (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
The concept of e-voting, which is to eliminates the need for manual paper ballots is gaining traction, particularly in large-scale implementations where security and reliability are crucial. Blockchain technology, recognized for its transformative impact across various industries, is increasingly being considered for its potential to enhance electoral systems through e-voting. This study aims to review the potential of blockchain technology in transforming e-voting systems, examines the prospects of blockchain-based e-voting systems, highlighting how blockchain’s core attributes; decentralization, immutability, and cryptographic security could address the significant challenges of traditional voting methods. By analyzing case studies, the advantages of blockchain in e-voting, and the various challenges involved, the work presents a roadmap for the adoption of blockchain-based e-voting as a means to strengthen democratic processes by enhancing transparency, security, and inclusivity.